1991
DOI: 10.1111/j.1600-0528.1991.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of caries increment in Scottish adolescents

Abstract: Salivary, clinical, and microbiological factors were compared with subsequent 2-yr caries increment in a group of 372 Scottish adolescents. The caries increment was significantly correlated with previous caries experience, salivary buffering capacity and counts of lactobacilli, mutans streptococci and candida. Veillonella levels and salivary flow rate were not correlated with caries increment. Significant improvements in the predictions were obtained when the results of more than one test were included using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
4
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 12 publications
8
34
4
2
Order By: Relevance
“…Our data were also in line with previous observations showing no correla- tion between the salivary secretion rate and the DMFT index [Birkhed and Heintze, 1989;Russell et al, 1990Russell et al, , 1991. A novel and interesting finding was that the salivary CA VI concentration exhibits a negative correlation with the DMFT index.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data were also in line with previous observations showing no correla- tion between the salivary secretion rate and the DMFT index [Birkhed and Heintze, 1989;Russell et al, 1990Russell et al, , 1991. A novel and interesting finding was that the salivary CA VI concentration exhibits a negative correlation with the DMFT index.…”
Section: Discussionsupporting
confidence: 82%
“…In dental caries, the hard tissues of the teeth are demineralized in the acidic environment produced by the bacterial metabolism. Salivary pH and buffering capacity are known to be central factors protecting teeth from caries [Birkhed and Heintze, 1989;Russell et al, 1990Russell et al, , 1991Wolinsky, 1994]. According to our present results, the salivary CA VI concentration seems to be as important a factor as the pH and buffering capacity in reducing the individual's susceptibility to caries (table 1).…”
Section: Discussionsupporting
confidence: 57%
“…Lactobacilli levels also have been used, but they do not seem to be as effective as caries predictors as the S. mutans. [25][26][27][28] In this study, salivary Lactobacilli weren't statistically different in the study and reference groups that support the Wahlin and Holm [29] and Ou-Yang et al results. [12] The effects of chemotherapy on human salivary glands and the composition of human saliva are difficult to assess, and available information is relatively sparse and often contradictory.…”
Section: Discussionsupporting
confidence: 75%
“…Studies on caries risk assessment have shown that past caries experience variables compared to other variables had a relatively strong association with caries increment and that caries experience was the best predictor of caries increment in children with a mixed dentition [Klock and Krasse, 1979;Honkala et al, 1984;Wilson and Ashley, 1989;Alaluusua et al, 1990;Russell et al, 1991;Disney et al, 1992;Alaluusua, 1993;Mattiasson-Robertson and Twetman, 1993;Raitio et al, 1996]. A recent study, which used the area under the ROC curve as a method to compare the prognostic accuracy of various predictors, has reported no appreciable effect when additional predictors such as mutans streptococci and lactobacilli counts, salivary flow rate, sucrose intake frequency, brushing frequency and social group were applied in combination with past caries experience [Hausen, 1997].…”
mentioning
confidence: 99%